Interpreting qualitative data / David Silverman. - Silverman, David, 1943- (Sage, 2024)
In his signature pragmatic and friendly style, David Silverman acts as your stand-in supervisor in the seventh edition of this book, taking you step-by-step through different methods for making sense of qualitative data. Whether you are interested in analysing visual images, interviews, focus groups or online data, this book provides a clear framework for using qualitative data to answer your research questions.